THE TEACHER’S QUESTIONING STRATEGIES TO ENCOURAGE STUDENTS’ RESPONSES IN ENGLISH CLASSROOM INTERACTION - Gomalla, Fourtha; Susilawati, Endang; Sumarni, Sumarni (JEELL (Journal of English Education, Linguistics and Literature) English Departement of STKIP PGRI Jombang, 2024)
This study aimed to find out the questioning strategies applied by the teacher as well as the functions of those strategies and the dominant questioning strategies used by the teacher to encourage students’ responses in English classroom interaction. This study was conducted at SMP Negeri 6 Pontianak with a descriptive qualitative method. The study was carried out by observing, interviewing, and taking video recordings of the English teacher that consisted of three meetings in the same class. The result showed that the teacher mostly used cueing strategies to encourage students’ responses in English classroom interaction. In addition, other strategies also used by the teacher were clueing, probing, and wait time. The teacher used those questioning strategies to check students’ understanding of the previous material, attract students’ attention and interest, ask for an explanation from students about the thing, and give time to students to think before answering the questions.